The effect of frailty on discharge location for Medicare beneficiaries after acute stroke - Seamon, Bryant A. (Arch Phys Med Rehabil, 2019)
OBJECTIVE: To examine the effect of frailty on post-stroke discharge location with respect to stroke severity and create a risk-adjusted model for understanding the effects of frailty on discharge to an inpatient rehabilitation facility. DESIGN: Retrospective cohort. SETTING: A 2014 5% Medicare Sample. PARTICIPANTS: 7258 patients hospitalized for a first-time acute ischemic stroke. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: A pre-hospitalization 6-month baseline was used to calculate a frailty score. Logistic regression to predict odds of discharge to inpatient rehabilitation was used to calculate for three levels of baseline frailty, controlling for patient demographics, stroke severity and co-morbidities. RESULTS: 1603 patients were discharged to inpatient rehabilitation. Patients who were non-frail (OR 1.716, 95%CI (1.463, 2.013) or pre-frail (OR 1.519, 95%CI (1.296, 1.779) were more likely to be discharged to inpatient rehabilitation. The final logistic regression model had a C-statistic of 0.63. The majority of patients discharged to inpatient rehabilitation were non-frail (44.2%) and had moderate strokes (38.9%). Individuals who were frail and suffered a moderate (OR 0.78, 95%CI (0.558, 1.091) or severe stroke (OR 0.509, 95%CI (0.358, 0.721) were less likely to be discharge to an inpatient rehabilitation facility. CONCLUSIONS: A lack of a claims-based measure for pre-stroke functional ability makes it difficult to understand discharge decision making patterns for individuals post-stroke. Pre-stroke frailty was found to have a significant effect on predicating inpatient rehabilitation discharge following an acute stroke when controlling for stroke severity, co-morbidities and age. Further investigation is warranted to examine differences in rehabilitation utilization based on frailty and to quantify the effect of rehabilitation on frailty status in individuals post-stroke.